Mapping unconventional Leishmania in human and animal leishmaniasis: A scoping review protocol on pathogen diversity, geographic distribution and knowledge gaps - Denis Sereno; Tahar Kernif; Renato Leon; Kholoud Kahime; Souad Guernaoui; Chaymaa Harkat; Mario J. Grijalva; Omar Hamarsheh; Anita G. Villacis; Bachir Medrouh; Thiago Vasconcelos Dos Santos; Razika Beniklef; et al. (PLoS ONE, 2025)
Introduction Leishmaniases are a vector-borne parasitic diseases with diverse clinical manifestations involving multiple Leishmania species and animal hosts. While most leishmaniasis cases are caused by a few well characterized Leishmania species, reports describe infections by unconventional or emerging Leishmania taxa, atypical clinical presentations from classical species, and occurrences of atypical Leishmania in animal hosts. These underrecognized infections present diagnostic and therapeutic challenges and are rarely reflected in surveillance systems or clinical guidelines. A systematic mapping of this evolving landscape is needed to guide future diagnostics, policy, and research priorities. Methods and analysis Following the Joanna Briggs Institute (JBI) methodology and PRISMA-ScR guidelines, we will search PubMed, Embase, Cochrane Library (CENTRAL), PROSPERO, Web of Science, and Global Index Medicus, as well as relevant grey literature. Eligible studies will include human cases with clinical presentations that diverge from those typically associated with well-characterized Leishmania species, reports involving unconventional or emerging Leishmania species, and animal cases of veterinary relevance caused by non-classical species, regardless of study design. Dual independent screening of records and data extraction using a standardized charting form will be conducted. Discrepancies between reviewers will be resolved by consensus. Data will be summarized descriptively through tables, figures, and thematic synthesis. Research gaps will be identified to inform future studies and public health strategies. Dissemination This review will use data from published sources and findings will be disseminated through publication in a peer-reviewed journal, presentations at scientific conferences, and sharing with relevant stakeholders. The results are intended to inform clinicians, researchers, and policymakers about the evolving landscape of leishmaniasis and to highlight priorities for future research and surveillance.